A Second Look at Automatic Theory of Mind: Reconsidering Kovács, Téglás, and Endress (2010). (September 2015) - Phillips, Jonathan; Ong, Desmond C.; Surtees, Andrew D. R.; Xin, Yijing; Williams, Samantha; Saxe, Rebecca; Frank, Michael C.
In recent work, Kovács, Téglás, and Endress (2010) argued that human adults automatically represented other agents' beliefs even when those beliefs were completely irrelevant to the task being performed. In a series of 13 experiments, we replicated these previous findings but demonstrated that the effects found arose from artifacts in the experimental paradigm. In particular, the critical findings demonstrating automatic belief computation were driven by inconsistencies in the timing of an attention check, and thus do not provide evidence for automatic theory of mind in adults.